2003
DOI: 10.1007/s00210-003-0752-1
|View full text |Cite
|
Sign up to set email alerts
|

Native somatostatin sst2 and sst5 receptors functionally coupled to Gi/o-protein, but not to the serum response element in AtT-20 mouse tumour corticotrophs

Abstract: Of the five cloned somatostatin (SRIF: somatotropin release inhibitory factor) receptors (sst1-5), only sst2 and sst5 receptors appear to be endogenously expressed and functionally active in AtT-20 mouse anterior pituitary tumour cells. In this study, the presence and the functional coupling of SRIF receptors to G-protein in AtT-20 cells was evaluated by receptor autoradiography and guanosine-5'-Omicron-(3-[35S]thio)-triphosphate ([35S]GTPgammaS) binding, respectively. In addition, transcriptional effects via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 44 publications
4
15
0
Order By: Relevance
“…Second, both SOM230 and Oct, as well BIM-23268, an sst 5 -preferring SRIF analog (Table 2), potently inhibited CRH-induced ACTH release, while maximal inhibition by SOM230 and BIM-23268 compared with Oct was significantly higher. Both sst 2 and sst 5 are known to be involved in the regulation of ACTH and cAMP production by AtT-20 cells [54] but, apparently, sst 5 seems to have functional superiority over sst 2 , which has been suggested by others as well [55].…”
Section: Novel Selective and Multiligand Srif-analogsmentioning
confidence: 95%
See 1 more Smart Citation
“…Second, both SOM230 and Oct, as well BIM-23268, an sst 5 -preferring SRIF analog (Table 2), potently inhibited CRH-induced ACTH release, while maximal inhibition by SOM230 and BIM-23268 compared with Oct was significantly higher. Both sst 2 and sst 5 are known to be involved in the regulation of ACTH and cAMP production by AtT-20 cells [54] but, apparently, sst 5 seems to have functional superiority over sst 2 , which has been suggested by others as well [55].…”
Section: Novel Selective and Multiligand Srif-analogsmentioning
confidence: 95%
“…Chronic glucocorticoid treatment of GH 4 C 1 cells, a clonal strain of rat pituitary tumor cells, and AtT20/D16 cells, a clonal strain of mouse corticotroph tumor cells, caused a 20-40% decrease in [ 125 I-Tyr 1 ]-SRIF binding [51]. Furthermore, with respect to SRIF and SRIF-analog mediated inhibitory effects on ACTH release by corticotroph tumor cells, numerous reports have been published in which consensus is found that SRIF, as well as sst 2 -and sst 5 -preferring SRIF analogs, lower ACTH release in mouse corticotroph tumor cells [52][53][54][55][56][57]. The consequences of SRIF receptor down-regulation by glucocorticoids on the biological responsiveness of corticotroph adenoma cells was demonstrated in primary cultures of human corticotroph adenomas, in which Oct-induced inhibition of basal and CRH-induced ACTH release, was abolished if the cells were pretreated with hydrocortisone [21].…”
Section: Srif In Corticotroph Adenomasmentioning
confidence: 95%
“…Among synthetic ligands, we used the peptidyl multiligand analog SOM230, which binds with high affinity to sst 1,2,3,5 [42][43][44], and the peptidyl multiligand analog KE108, which binds with high affinity to all five SRIF receptors [44,45]. The sst 1 -selective peptidyl agonist CH-275 [35,41,46,47], the sst 2 -preferring peptiydyl agonist SMS 201-995 (also known as sandostatin or octreotide) [38,41,46,48,49], and the sst 2 -selective nonpeptidyl agonist L-779,976 [46, 49 -51] were also used in the absence or presence of the sst 1 -selective nonpeptydil antagonist SRA-880 [46,52,53] and the sst 2 -selective peptydil antagonist CYN [36,38,48,49,54]. All compounds were applied at 1 M, which from previous studies, is a concentration giving maximal re- ceptor occupancy [2,41].…”
Section: Expression Of Srif Receptor Mrnas In Human Macrophagesmentioning
confidence: 99%
“…IC 50 values of inhibition suggested a sst 5 -like response of ACTHinhibition. Both sst 2 and sst 5 are involved in the inhibition of ACTH release and cAMP production in AtT20 cells [56] and a functional superiority of sst 5 over sst 2 has been suggested by others as well [57,58]. On the other hand, sst 2 receptors, albeit at low level, are co-expressed with sst 5 receptors in corticotroph adenomas as well.…”
Section: Role Of Somatostatin and Its Analogs On Acth Secretion By Comentioning
confidence: 77%